2012
DOI: 10.3406/revec.2012.1965
|View full text |Cite
|
Sign up to set email alerts
|

Grazing exclosure and plantation: a synchronic study of two restoration techniques improving plant community and soil properties in arid degraded steppes (Algeria)

Abstract: Steppes of arid Mediterranean zones are deeply threatened by desertification. To stop or alleviate ecological and economic problems associated with this desertification, management actions have been implemented since the last three decades. The struggle against desertification has become a national priority in some of these countries. In Algeria, several management techniques have been used to cope with desertification. This study aims to investigate the effect of two management techniques on vegetation, soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
1
Order By: Relevance
“…But, they also found that long-term grazing exclusion had a negative effect on the diversity and abundance of soil bacteria. The comparison of soil physicochemical parameters and the floristic richness between grazed and short-term grazing exclusion in arid degraded steppes showed significant variations in coarse elements, sand, and biodiversity (Amghar et al, 2012;Kouba et al, 2021). But, there was no variation in soil chemical characteristics.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…But, they also found that long-term grazing exclusion had a negative effect on the diversity and abundance of soil bacteria. The comparison of soil physicochemical parameters and the floristic richness between grazed and short-term grazing exclusion in arid degraded steppes showed significant variations in coarse elements, sand, and biodiversity (Amghar et al, 2012;Kouba et al, 2021). But, there was no variation in soil chemical characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…However, the situation of the soils of North African steppe ecosystems, and in particular those of Algeria, is poorly understood and very little studied in the context of different temporal scales of land degradation due to grazing pressures inducing plant cover changes, which are constantly increasing in order to meet growing socioeconomic needs. In North Africa, studies that have investigated the fate of soil properties in degraded steppes are very rare (Aidoud et al, 1999;Jeddi and Chaieb, 2010;Amghar et al, 2012;Neffar et al, 2013;Hasnaoui and Bouazza, 2015;Neffar et al, 2022). The scientific questions addressed in this study are as follows: 1) does the degradation of steppe vegetation induce degradation or significant change in soil characteristics?…”
Section: Introductionmentioning
confidence: 96%
“…Here, it is well recognized that anthropogenic practices such as overgrazing is counted as one of the major problems that the steppe courses are exposed to. Overgrazing might allow a regeneration of the vegetation but with a low pastoral value in comparison with another technique of restoration like the pastoral plantations (Amghar et al, 2012). In fact, the increase of the population and their livestock numbers was followed further by a sedentarization that had a high pressure in the rangelands, con rmed Martínez-Valderrama et al, (2017).…”
Section: Introductionmentioning
confidence: 86%
“…In spring 2022, outside the HDM site, this difference can be attributed to the abundance of Thymelaea mycrophylla Coss. & Durieu, with a density of 4.2 plants per square meter, explained by the species' ability to withstand harsh conditions and their low quality and palatability index [31]. Additionally, Helianthemum kahiricum is the most abundant and dominant species within the HZM site (fully enclosed), accounting for over 80% of the total density.…”
Section: Plant Densitymentioning
confidence: 99%